“Un hombre contra un continente. José Abascal, Rey de América (1806-1816)”, de Juan Ignacio Vargas Ezquerra. - de la Torre López, Arturo E. (Naveg@mérica, 2010)
“Un hombre contra un continente. José Abascal, Rey de América (1806-1816)”, de Juan Ignacio Vargas Ezquerra.